Characterization of the RpoN regulon reveals the regulation of motility, T6SS2 and metabolism in Vibrio parahaemolyticus - Gu, Dan; Zhang, Youkun; Wang, Kangru; Li, Mingzhu; Jiao, Xinan (Frontiers in Microbiology, 2022)
Vibrio parahaemolyticus is a foodborne pathogen that can colonize the small intestine of the host and cause diarrhea. The alternative sigma factor RpoN plays a vital role in regulating motility, carbon utilization and affects host colonization in V. parahaemolyticus RIMD2210633. In this study, transcriptome and phenotypic analysis further expanded our understanding of the RpoN regulon in V. parahaemolyticus. A deletion mutant of rpoN (ΔrpoN) was subjected to RNA-seq for systemic identification of the RpoN-controlled genes. Compared with the wild-type (WT), 399 genes were differentially expressed in the ΔrpoN strain. Moreover, 264 genes were down-regulated in the ΔrpoN strain, including those associated with nitrogen utilization (VP0118), glutamine synthetase (VP0121), formate dehydrogenase (VP1511 and VP1513-VP1515), quorum sensing (opaR and luxZ), polar flagellar systems, and type VI secretion system 2 (T6SS2). Quantitative real-time reverse transcription PCR (qRT-PCR) and electrophoretic mobility shift assay (EMSA) further confirmed that RpoN could directly bind to the promoters of these genes associated with polar flagellar systems (flgB and fliE), lateral flagellar systems (flgB2 and lafA), T6SS2 (hcp2 and VPA1044) and glutamine synthetase (VP0121), and then positively regulate the expression of these systems. A RpoN-binding motif was identified in V. parahaemolyticus using the MEME suite and verified by the EMSA. Besides, the deletion of rpoN caused a significant decrease in hemolytic activity, adhesion, and cytotoxicity. Our results provide new cues to better understand the regulatory networks of RpoN protein to motility, T6SS2, and metabolism in V. parahaemolyticus.